Method for Transformation of Weak Magnetic Minerals (Hematite, Goethite) into Strong Magnetic Mineral (Magnetite) to Improve the Efficiency of Technologies for Oxidized Iron Ore Beneficiation - Ponomarenko, O.M.; Brik, A.B.; Dudchenko, N.O.; Yushin, O. (Science and Innovation, 2024)
A new method for relatively simple transformation of the weak magnetic minerals (goethite (α-FeOOH) and hematite (α-Fe2O3)) into the strong magnetic mineral (magnetite (Fe3O4)) has been developed. The structure and magnetic characteristics of goethite and hematite have been showed to transform in the presence of starch at relatively low temperatures (in the range of 300–600 °С). The results obtained have opened up new opportunities for the development of effective technologies for oxidized iron ore beneficiation.